THE COMMUNITYâ€™S STIGMA CAUSE OF DECREASE VISITING â€œXâ€ HOSPITAL IN COVID-19 PANDEMIC - Megawati, Devvy; Erziâ€™, Alfan; Ratri, Devita Rahmani (Fakultas Kedokteran Universitas Brawijaya)
â€œXâ€ hospital Tulungagung is a class D with madya accredited hospital in collaboration health BPJS.